Sustainability of community-based workers in multisectoral food security programs: a case study of producer leaders, village vaccinators, mother leaders, and community health workers in Burkina Faso. - Wilson, K. R; Rogers, B. L; Carroll, D. A; Ezaki, A.; Coates, J. (Tufts University. Tisch Library., 2023)
Keywords: Food security, Community development, Community-based workers (CBWs), Agricultural development, Sustainability.; Springer Open.